2000
DOI: 10.1101/gr.145200
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Maps of Human 19p13.3 and Mouse Chromosome 10 Allow Identification of Sequences at Evolutionary Breakpoints

Abstract: A cosmid/bacterial artificial chromosome (BAC) contiguous (contig) map of human chromosome (HSA) 19p13.3 has been constructed, and over 50 genes have been localized to the contig. Genes and anonymous ESTs from ≈4000 kb of human 19p13.3 were placed on the central mouse chromosome 10 map by genetic mapping and pulsed-field gel electrophoresis (PFGE) analysis. A region of ∼2500 kb of HSA 19p13.3 is collinear to mouse chromosome (MMU) 10. In contrast, the adjacent ≈1200 kb are inverted. Two genes are located in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…There is evidence of at least 3170 microrearrangements (reversals) that happened within the synteny blocks (although many of them may be artifacts of incorrect assemblies). This very high estimate of the number of microrearrangements further confirms the conjecture that microrearrangements are more common than previously thought (Carver and Stubbs 1997;Puttagunta et al 2000;Thomas et al 2000;Kumar et al 2001). In fact, this number does not even include the microrearrangements within synteny blocks shorter than 1 Mb.…”
Section: Synteny Blockssupporting
confidence: 85%
“…There is evidence of at least 3170 microrearrangements (reversals) that happened within the synteny blocks (although many of them may be artifacts of incorrect assemblies). This very high estimate of the number of microrearrangements further confirms the conjecture that microrearrangements are more common than previously thought (Carver and Stubbs 1997;Puttagunta et al 2000;Thomas et al 2000;Kumar et al 2001). In fact, this number does not even include the microrearrangements within synteny blocks shorter than 1 Mb.…”
Section: Synteny Blockssupporting
confidence: 85%
“…Multiple evolutionary breakpoints between the human and mouse genomes have been examined at the sequence level (Lund et al 2000;Dehal et al 2001;Puttagunta et al 2000). In many cases, these breakpoint sequences were found to be enriched for simple-sequence repeats and L1 repetitive elements or associated with clustered gene families, gene family expansions, and more limited gene duplications.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Puttagunta et al (2000) and Pletcher et al (2000) on evolutionary breakpoints in mouse chromosome 10 showed an association with a region of very high (60%-70%) repeated sequence content and Dehal et al (2001) found a concentration of LINEs and LTR elements at evolutionary breakpoints. Consideration of the gross distribution of repeated elements, including simple repeats, and base composition in segment 5 (the breakpoint region) as a whole compared with the rest of the Del36H sequence, showed no apparent associations.…”
Section: Sites Of Evolutionary Rearrangementmentioning
confidence: 95%
“…The accumulating information on genome sequences from a number of species raises many questions about genome evolution. Important among these are the relative roles of whole-genome, segmental, and individual gene duplication, and the mechanisms underlying these processes (Lynch and Conery 2000; Dehal et al 2001;Eichler and Sankoff 2003;Friedman and Hughes 2004); the usefulness of inter-genome comparisons for identifying selectively conserved regions in genomes, including not only genes, but regulatory regions and functional RNA genes (Mallon et al 2000;Dehal et al 2001;Dermitzakis et al 2002;Kondrashov and Shabalina 2002;Margulies et al 2003;Frazer et al 2004); the roles of repeated (transposable element-like) and repetitive (satellites, microsatellites, and minisatellites) sequences in genome evolution (Toth et al 2000;Hancock 2002;Babcock et al 2003;Alba and Guigo 2004;Han et al 2004;Kazazian Jr. 2004); and the characteristics of sites of evolutionary chromosome breakpoints (Puttagunta et al 2000;Dehal et al 2001;Pevzner and Tesler 2003).…”
mentioning
confidence: 99%